Megastigmans and other compounds from Antidesma hainanensis Merr - Viet Cuong, Le Canh; Trang, Do Thi; Nhiem, Nguyen Xuan; Yen, Pham Hai; Tai, Bui Huu; Tuan Anh, Hoang Le; Huong, Le Mai; Minh, Chau Van; Kiem, Phan Van (Vietnam Journal of Chemistry, 2016)
Four megastigmans 7-megastigmene-3-ol-9-one 3-O-[α-L-arabinofuranosyl-(1→6)-β-D-glucopyranoside]  (1),  alangionoside L (2),  alangioside (3), ampelopsisionoside (4), and other constituents as N–trans-feruloyloctopamide (5), trans-linalool-3,6-oxide-β-D-glucopyranoside (6),  5α,8α-dipioxiergosta-6,22-diene-3β-ol (7), and (Z)-2-hexenyl β-D-glucopyranoside (8) were isolated from the methanol extract of the Antidesma hainanensis leaves. Their chemical structures were successfully determined using NMR and ESI-MS analysis as well as in comparison with the reported data. This is the first report of these compounds from Euphorbiaceae family